In-situ formed elastin-based hydrogels enhance wound healing via promoting innate immune cells recruitment and angiogenesis. (June 2022) - Tian, Duo-Mei; Wan, Huan-Huan; Chen, Jia-Reng; Ye, Yong-Bin; He, Yong; Liu, Yu; Tang, Lu-Yao; He, Zhong-Yuan; Liu, Kai-Zheng; Gao, Chong-Jian; Li, Sheng-Lin; Xu, Qian; et al.
Abstract: Harnessing the inflammation and angiogenesis is extremely important in wound healing. In this study, we developed bioactive elastin-based hydrogels which can recruit and modulate the innate immune cells and accelerate angiogenesis in the wound site and subsequently improve wound regeneration. These hydrogels were formed by visible-light cross-linking of acryloyl-(polyethylene glycol)-N-hydroxysuccinimide ester modified elastin with methacrylated gelatin, in order to mimic dermal microenvironment. These hydrogels showed highly tunable mechanical properties, swelling ratios and enzymatic degradation profiles, with moduli within the range of human skin. To mimic the in vivo degradation of the elastin by elastase from neutrophils, in vitro co-culture of the hydrogels and neutrophils was conducted. The derived conditioned medium containing elastin derived peptides (EDP-conditioned medium) promoted the expression of both M1 and M2 markers in M1 macrophages in vitro . Additionally, the EDP-conditioned medium induced superior tube formation of endothelia cells in Matrigel. In mice wound model, these elastin-based hydrogels attracted abundant neutrophils and predominant M2 macrophages to the wound and supported their infiltration into the hydrogels. The outstanding immunomodulatory effect of the elastin-based hydrogels resulted in superior angiogenesis, collagen deposition and dermal regeneration. Hence, these elastin-based hydrogels can be a promising regenerative platform to accelerate wound repair. Graphical abstract: Elastin-based hydrogels were synthesized by blue-light crosslinking of modified elastin and GelMA, and then applied in mice dermal wound. During inflammation stage of wound healing, innate immune cells neutrophils and macrophages arrive in the wound site. The neutrophils secret neutrophil elastase to degrade the hydrogels, resulting in accelerated elastin-derived peptides (EDPs) release and facilitating the infiltration of neutrophiles and macrophages into the hydrogels. The proangiogenic factors produced by the innate immune cells and the EDPs work together to promote angiogenesis and tissue growth in the wound, and eventually accelerated wound healing is achieved. Image 1